GEOGRAPHIC INFORMATION SYSTEM MAPPING SENIOR HIGH SCHOOL AND VOCATIONAL HIGH SCHOOL IN BALI ISLAND BASED INTERNET BY USING GOOGLE MY MAPS - Supuwiningsih, Ni Nyoman; Malau Pase, Adam Sheni Martua (International Journal of Engineering Technologies and Management Research, 2022)
This study aims to provide information to prospective students and the public about mapping the profiles of SMA (Senior High School) and SMK (Vocational High School) on the island of Bali online through google my map to assist in making decisions in choosing the school as desired because at the time of school selection based on the zoning system. The method used in this study is a field research method which consists of several stages in the flow of analysis, namely Literature Study, Spatial data collection, Internet-based digital map creation using Google My Maps, Integration of spatial data and non-spatial data and implementation. Integration of spatial data and non-spatial data for SMA and SMK in the form of a digital map based on a Geographic Information System using Google My Maps software and a comparison of the number of SMA and a comparison of SMK spread across several regencies /municipalities where almost every regency/municipality has a number of SMA and the number of Vocational High School balanced, based on the results of the analysis that the number of SMA and the number of SMK that are spread out are for SMA and SMK on the island of Bali, namely 179 and 178 with a comparison of about 50.1% for SMA and around 49.9% for SMK. This study focuses on the dissemination of information for high school and vocational schools that are integrated with school profile information packaged in the concept of a Geographic Information System using google my map which can be accessed by prospective new students to decide to choose a school based on the zoning system or distance from where they live.